Elementary Mathematics Curriculum Materials Designs for Student Learning and Teacher Enactment - Remillard, Janine T.; Kim, Ok-Kyeong (Research in Mathematics Education, 2020)
XX, 321 p. 61 illus., 47 illus. in color.